The Cultivation of Music Teachers in Primary and Secondary Schools and the Trend of Continuing Professional Development, China - Pengxiang, Ma; Pattananon, Nicha; Intrakamhaeng, Siriwan (Journal of Modern Learning Development, 2023)
Presently, the proportion of the requirements of the Chinese government for aesthetic education in primary and secondary education is increasing, which promotes the teaching reform of normal colleges and universities, and also increases the proportion of professionalism and value of this position. However, on the other hand, this measure has significantly improved the employment requirements for normal university students, not only to have perfect knowledge and ability in subject teaching but also put forward new requirements in aesthetic education. This article states the cultivation of music teachers in primary and secondary schools and the trend of continuing professional development in China.